Enhanced Lung Cancer Detection Using ANN with Random Oversampling, RFE-Based Feature Selection, and GridSearchCV Hyperparameter Tuning - Nurwafiqah Nurwafiqah; M. Yudi Al Fiqran; Annisa Nurul Puteri; Muhammad Arafah; Tatik Maslihatin; A. Sumardin (Informatika, Universitas Jenderal Soedirman, 2026)
Amid the most predominant mortality factors on a global scale, Lung cancer constitutes one of the most significant oncological burdens, chiefly because most patients receive a diagnosis only at later stages. The limitations of conventional diagnostic approaches underscore the urgent need for artificial intelligence–based detection systems that can improve both diagnostic accuracy and efficiency. This study aims to develop a lung cancer prediction model using an Artificial Neural Network (ANN) optimized through an integrated strategy that includes data preprocessing, class balancing via Random Oversampling (ROS), feature selection using Recursive Feature Elimination (RFE), and hyperparameter tuning with Grid Search. The evaluation of model effectiveness employs accuracy, precision, recall, F1-score, along with a confusion matrix. Experimental results demonstrate an accuracy of 98%, with average precision, recall, and F1-score values of 0.95. Statistical validation using McNemar’s test confirms a significant performance improvement over the baseline model (χ² = 18.05, p < 0.001), accompanied by a large effect size (Cohen’s h = 0.82). Furthermore, the model exhibits balanced performance in identifying both lung cancer and non-cancer cases, reflecting the effectiveness of the data balancing and feature selection strategies. These findings suggest that the optimized ANN model has strong potential as a foundation for a medical decision support system for early lung cancer detection, contributing to more reliable diagnoses and more accurate clinical decision-making.